Acyclic Pseudopeptidic Hosts as Molecular Receptors and Transporters for Anions. Issue 23 (3rd July 2015) - Martí, Inés; Burguete, M. Isabel; Gale, Philip A.; Luis, Santiago V.
Abstract: The synthesis and characterization of different pseudopeptidic hosts derived from open chain systems with C 2 and C 3 symmetry has been achieved. These receptors are based on structures containing phenylalanine amino acid residues and amine, amide, urea and thiourea groups as the structural elements providing their capability to interact with anions. The transport of chloride and organic anions of biological relevance (L ‐lactate, L ‐maleate andL ‐aspartate) through lipid bilayer membranes has been studied for these receptors. The chloride‐binding properties of the selected hosts have been studied in solution by NMR titrations. In addition, in order to rationalize the results, lipophilicity studies have been carried out. It has been observed that transport activity is affected by the nature of the aliphatic central spacer and the side chains, the most active receptors being9b, derived from a tripodal precursor with the shortest aliphatic side chain and3c, derived from a bis(amino amide) but having the longest spacer. These hosts are more selective for the anion chloride than for the studied organic anions. Abstract : Pseudopeptidic structures offer access to the design of efficient anion transmembrane carriers.